2018
DOI: 10.1038/s41598-018-21073-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces pulmonary fibroblast proliferation through NFAT signaling

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive and typically fatal lung disease with a very low survival rate. Excess accumulation of fibroblasts, myofibroblasts and extracellular matrix creates hypoxic conditions within the lungs, causing asphyxiation. Hypoxia is, therefore, one of the prominent features of IPF. However, there have been few studies concerning the effects of hypoxia on pulmonary fibroblasts. In this study, we investigated the molecular mechanisms of hypoxia-induced lung fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 62 publications
(85 reference statements)
2
69
0
Order By: Relevance
“…4). This is consistent with previous studies which have reported hypoxia results in dependence on glycolysis for cell proliferation 54 . A recent glycoproteomic analysis performed on the isogenic human OS cell lines, HOS and 143B, also indicated upregulation of glycolysis/PPP proteins in the highly metastatic 143B cell line 55 .…”
Section: Discussionsupporting
confidence: 94%
“…4). This is consistent with previous studies which have reported hypoxia results in dependence on glycolysis for cell proliferation 54 . A recent glycoproteomic analysis performed on the isogenic human OS cell lines, HOS and 143B, also indicated upregulation of glycolysis/PPP proteins in the highly metastatic 143B cell line 55 .…”
Section: Discussionsupporting
confidence: 94%
“…Proliferation of myofibroblasts is a key feature of wound healing and adverse fibrosis 6,31 . In the present study, we observed upregulated levels of proliferation marker MKI67 32,33 under hypoxic conditions, consistent with other reports, showing increased hypoxia-mediated proliferation of cardiac 20 and pulmonary fibroblasts 34 . The strongly reduced expression of MKI67 ascribed Rhein a novel anti-proliferative property in regard to cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…Hypoxia is another feature in IPF (Kawakami, Mimura, Shoji, Tanaka, & Nangaku, ; Tzouvelekis et al, ). We and others have shown that hypoxia stimulates lung fibroblast proliferation (Bodempudi et al, ; Mizuno et al, ; Senavirathna et al, ). There is evidence that hypoxia and TGFβ signaling cross‐talk to promote fibrosis (Abdul‐Hafez, Shu, & Uhal, ; Qian et al, ; Ueno et al, ).…”
Section: Introductionmentioning
confidence: 81%